The deconvolution of lunar brightness temperature based on the maximum entropy method using Chang'e-2 microwave data. (1st February 2015) - Xing, Shu-Guo; Su, Yan; Feng, Jian-Qing; Li, Chun-Lai
Abstract A passive and multi-channel microwave sounder onboard the Chang'e-2 orbiter has successfully acquired microwave observations of the lunar surface and subsurface structure. Compared with the Chang'e-1 orbiter, the Chang'e-2 orbiter obtained more accurate and comprehensive microwave brightness temperature data, which are helpful for further research. Since there is a close relationship between microwave brightness temperature data and some related properties of the lunar regolith, such as the thickness, temperature and dielectric constant, precise and high resolution brightness temperature data are necessary for such research. However, through the detection mechanism of the microwave sounder, the brightness temperature data acquired from the microwave sounder are weighted by the antenna radiation pattern, so the data are the convolution of the antenna radiation pattern with the lunar brightness temperature. In order to obtain the real lunar brightness temperature, a deconvolution method is needed. The aim of this paper is to solve the problem associated with performing deconvolution of the lunar brightness temperature. In this study, we introduce the maximum entropy method (MEM) to process the brightness temperature data and achieve excellent results. The paper mainly includes the following aspects: first, we introduce the principle of the MEM; second, through a series of simulations, the MEM has been verified as an efficient deconvolution method; and third, the MEM is used to process the Chang'e-2 microwave data and the results are significant.